PENGEMBANGAN PRODUK MENGGUNAKAN DESIGN THINKING PADA MASA PANDEMI COVID-19 - Rayyan Sugangga (Jurnal Akademika, 2020)
Covid-19 pandemic has disrupted the business world, many countries have improved recession. This crisis requires every business or company must conduct its business wheels, one of them by doing products or services. Design according to thought can be done by design methods. This article discusses the application design that thinks with real case studies and observations. From this research it can be concluded that design thinking is very relevant to be applied in a crisis era, and even agreed to be a consideration for every business or company to use and apply this method.Keywords: Design Thinking, Crisis, Prototyping, Iteration, Innovation